International Trade Outlook for Latin America and the Caribbean 2022 - Economic Commission for Latin America; the Caribbean (United Nations, 2023)
In its 2022 edition, this ECLAC annual report examines the foreign trade performance of the region’s economies during the year. It consists of three chapters. The first examines recent developments in global and regional trade amid the conflict between the Russian Federation and Ukraine, record-high inflation rates, the global economic slowdown, geopolitical tensions and the difficulties faced by China in containing the COVID-19 pandemic. Chapter II presents an overview of the region’s foreign trade in manufactures in the past three decades, with particular emphasis on its export performance. Chapter III discusses the profound disruptions observed in global shipping supply chains since the onset of the pandemic, which have been exacerbated by the conflict between the Russian Federation and Ukraine.